Obesity-Induced Endoplasmic Reticulum Stress Causes Lung Endothelial Dysfunction and Promotes Acute Lung Injury - Shah, Dilip (Am J Respir Cell Mol Biol, 2017)
Obesity is a significant risk factor for acute respiratory distress syndrome. The mechanisms underlying this association are unknown. We recently showed that diet-induced obese mice exhibit pulmonary vascular endothelial dysfunction, which is associated with enhanced susceptibility to LPS-induced acute lung injury. Here, we demonstrate that lung endothelial dysfunction in diet-induced obese mice coincides with increased endoplasmic reticulum (ER) stress. Specifically, we observed enhanced expression of the major sensors of misfolded proteins, including protein kinase R-like ER kinase, inositol-requiring enzyme α, and activating transcription factor 6, in whole lung and in primary lung endothelial cells isolated from diet-induced obese mice. Furthermore, we found that primary lung endothelial cells exposed to serum from obese mice, or to saturated fatty acids that mimic obese serum, resulted in enhanced expression of markers of ER stress and the induction of other biological responses that typify the lung endothelium of diet-induced obese mice, including an increase in expression of endothelial adhesion molecules and a decrease in expression of endothelial cell–cell junctional proteins. Similar changes were observed in lung endothelial cells and in whole-lung tissue after exposure to tunicamycin, a compound that causes ER stress by blocking N-linked glycosylation, indicating that ER stress causes endothelial dysfunction in the lung. Treatment with 4-phenylbutyric acid, a chemical protein chaperone that reduces ER stress, restored vascular endothelial cell expression of adhesion molecules and protected against LPS-induced acute lung injury in diet-induced obese mice. Our work indicates that fatty acids in obese serum induce ER stress in the pulmonary endothelium, leading to pulmonary endothelial cell dysfunction. Our work suggests that reducing protein load in the ER of pulmonary endothelial cells might protect against acute respiratory distress syndrome in obese individuals.